2014
DOI: 10.5114/wiitm.2014.45437
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and ghrelin and leptin changes after sleeve gastrectomy.

Abstract: IntroductionSurgical intervention in obesity is today the most effective treatment method in high level obesity management. Bariatric interventions not only ensure body weight reduction, but may influence dietary habits.AimTo assess changes in adipose hormones and dietary habits in obese patients after sleeve gastrectomy.Material and methodsThe study set comprised 37 subjects (29 females and 8 males) 24 to 68 years old with body mass index 43.0 ±4.9 kg/m2. Pre-operative examination included baseline measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
2
24
0
3
Order By: Relevance
“…We evaluated the evolution of body composition and observed that, in both surgeries, total FFM decreased until 3 months and then stabilized, whereas total FM displayed a continuous decrease during the followup. Our results are consistent with previous reports showing changes in body composition following GBP [22] or SG [36] as measured by DXA. Our results are also concordant with the only study comparing these outcomes after both sleeve and bypass [19].…”
Section: Discussionsupporting
confidence: 95%
“…We evaluated the evolution of body composition and observed that, in both surgeries, total FFM decreased until 3 months and then stabilized, whereas total FM displayed a continuous decrease during the followup. Our results are consistent with previous reports showing changes in body composition following GBP [22] or SG [36] as measured by DXA. Our results are also concordant with the only study comparing these outcomes after both sleeve and bypass [19].…”
Section: Discussionsupporting
confidence: 95%
“…In support of this contention, we recently discovered that RYGB rats with reduced circulating ghrelin had diminished GHSR control of dopamine neuronal firing , suggesting that reduced plasma ghrelin may lead to reductions in central GHSR function. A significant decrease in leptin receptor mRNA expression was also observed in the hypothalamus of VSG rats, an observation in agreement with decreased circulating leptin hormone following VSG . It is important to note that leptin concentration and sensitivity closely correlate with body weight as obesity increases, whereas weight loss decreases plasma leptin levels .…”
Section: Discussionsupporting
confidence: 74%
“…Our review showed that leptin level has the tendency to decrease after different types of bariatric operations [88][89][90][91].…”
Section: Resultsmentioning
confidence: 82%
“…A number of long-term studies have shown that in RYGB and LSG operations a comparable reduction in patient body weight occurs, but the ghrelin level increases in RYGB and decreases in LSG. Therefore, the level of ghrelin does not affect weight loss [88,90,91]. Surgery-mediated modulation of brain function via modified postoperative secretion of gut peptides and vagal nerve stimulation was identified as an underlying mechanism in weight loss and improvement of weight-related diseases.…”
Section: Resultsmentioning
confidence: 99%